Establishment of antiretroviral pediatric registry: efforts toward achieving the UNAIDS 95-95-95 targets in the Free State Province, South Africa - Omotoso, Bukola R.; Dheda, Mukesh; Sempa, Joseph B.; Tabane, Elizabeth; Baleni, Refuoe; Jiane, Tshepang; Mofokeng, Thabiso R. (Frontiers in Public Health, 2025)
Globally, there are approximately 1·5 million children (0–14 years old) living with human immunodeficiency virus/acquired immunodeficiency syndrome (HIV/AIDS), of which 90% are in sub-Saharan Africa. South Africa has the most extensive pediatric HIV care and treatment program. Statistical data from 2023 demonstrated that 152,984 South African children (<15 years) were living with HIV. Despite the remarkable progress toward achieving the UNAIDS 95-95-95 targets in South African adults, the progress in the pediatric population seems to be lagging. HIV/AIDS remains a major factor in the morbidity and mortality of children. Some of the challenges impacting successful treatment outcomes include a high rate of loss to follow-up, virological non-suppression, and difficulties with treatment adherence as the children are reaching adulthood, indicating an urgent need for improved quality of care for children on antiretroviral therapy. The occurrence of adverse drug reactions (ADRs) is one of the problems affecting patient retention in treatment and is associated with an increased risk of incomplete viral suppression. To address these issues, strengthening spontaneous ADR reporting among HIV-infected pediatric patients at healthcare facilities has contributed to developing strategies for the prediction, identification, reporting, and prevention of ADR occurrence. In addition, establishing the ARV-Pediatric Registry has improved the quality of care for children on ART by enabling timely interventions and monitoring the effectiveness and safety of ART. These initiatives will help to address the specific challenges associated with reaching the 95-95-95 targets and provide a pathway forward for sustainable healthcare delivery for this vulnerable population.